Contribution of Arbuscular Mycorrhizal Fungi (AMF) in Improving the Growth and Yield Performances of Flax (Linum usitatissimum L.) to Salinity Stress - Ioanna Kakabouki; Panteleimon Stavropoulos; Ioannis Roussis; Antonios Mavroeidis; Dimitrios Bilalis (Agronomy, 2023)
Throughout the world, salinity is a major environmental issue that limits agricultural productivity, particularly in arid and semi-arid regions. In addition, climate change is the most important reason for the salinization of agricultural soils in the world, so it is now essential to find solutions to increase salinity tolerance in plants. This study investigated the potential of arbuscular mycorrhizal fungi (AMF) inoculation to enhance the growth and yield performances of flax under different salinity levels by conducting a pot experiment. The experiment was laid out in a two-factor completely randomized design including AMF inoculation (AMF+: with inoculation; AMF−: without inoculation) and irrigation water salinity (0, 50, 100, and 150 mM NaCl). According to the results, it is evident that salt stress caused negative physiological effects, including limited growth, reduced photosynthesis, and decreased nitrogen (N) and phosphorus (P) content in the shoots and roots of flax plants. Moreover, mycorrhizal association improved the salt tolerance of the plants by increasing chlorophyll content, and enhancing N and P shoot and root contents and consequently yield parameters, such as seed and stem fiber yield, particularly at moderate salt concentrations (50 and 100 mM NaCl). In particular, under 100 mM, AMF increased the total chlorophyll content, N shoot and root content, P shoot and root content, and seed and stem fiber yield by 30.4%, 36.1%, 31.0%, 38.9%, 45.4%, 35.2%, and 26.9%, respectively. As a result of using AMF, flax plants grown under salt stress exhibited tolerance, suggesting that AMF could be applied in saline environments to maintain ecological stability.